Aberrant Lipid Metabolism in Cancer: Current Status and Emerging Therapeutic Perspectives - Irshad, Rasha; Tabassum, Sazi; Husain, Mohammad (Current Topics in Medicinal Chemistry, 2023)
It is now an undisputed fact that cancer cells undergo metabolic reprogramming to support their malignant phenotype, and it is one of the crucial hallmarks which enables cancer cells to facilitate their survival under variable conditions ranging from lack of nutrients to conditions, such as hypoxia. Recent developments in technologies, such as lipidomics and machine learning, have underlined the critical effects of altered lipid metabolism in tumorigenesis. The cancer cells show elevated de novo fatty acid synthesis, an increased capacity to scavenge lipids from their environment, and enhanced fatty acid oxidation to fulfill their need for uncontrolled cellular proliferation, immune evasion, tumor formation, angiogenesis, metastasis, and invasion. Besides, important genes/ proteins involved in lipid metabolism have been proposed as prognostic indicators in a variety of cancer types linked to tumor survival and/or recurrence. Consequently, several approaches are being explored to regulate this metabolic dysregulation to subvert its tumorigenic properties in different types of cancers. The present review details the significance of lipid metabolism in cancer progression, the critical enzymes involved therein, and their regulation. Moreover, the current findings of the interplay between the oncogenic pathways and the lipid metabolic enzymes are elucidated briefly. The therapeutic implications of modulating these aberrations for the advancement of anti-cancer therapies are also discussed. Although the understanding of altered lipid metabolism in cancer initiation and progression is still in its infancy and somewhat obscure, its in-depth comprehension will open promising therapeutic opportunities for the development of novel and promising strategies for cancer treatment and management.
Keywords: Fatty acid synthesis